Production of 3D-Printed Tympanic Membrane Scaffolds as a Tissue Engineering Application - ŞAHİN, ALİ; OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; KILIÇ, OSMAN (Springer, 2020)
In recent years, scaffolds produced in 3D printing technology have become more widespread tool due to providing more advantages than traditional methods in tissue engineering applications. In this research, it was aimed to produce patches for the treatment of tympanic membrane perforations which caused significant hearing loss by using 3D printing method. Polylactic acid (PLA) scaffolds with Chitosan (CS) added in various ratios were prepared for artificial eardrum patches. Different amounts of CS added to PLA to obtain more biocompatible scaffolds. The created patches were designed by mimicking the thickness of the natural tympanic membrane thanks to the precision provided by the 3D printed method. The produced scaffolds were analyzed separately for physical, chemical, morphological, mechanical and biocompatibility properties. Human adipose tissue-derived mesenchymal stem cells (hAD-MSCs) were used for cell culture study to analyze the biocompatibility properties. 15 wt% PLA was chosen as the control group. Scaffold containing 3 wt% CS demonstrated significantly superior and favorable features in printing quality. The study continued with these two scaffolds (15PLA and 15PLA/3CS). This study showed that PLA and PLA/CS 3D printed scaffolds are a potential application for repairing tympanic membrane perforation. © Springer Nature Switzerland AG 2020.
Keywords: 3D printing; Biomaterials; Tissue engineering; Tympanic membrane patch